FUZZY LOGIC UNTUK PENYAKIT KOLESTEROL DALAM PENGAMBILAN GOLONGAN OBAT - Jasri oc (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
Eating fried foods or eating oily oils causes fat build up, which causes cholesterol. Often Eating people do not know the cause of cholesterol and many people who are wrong in taking drugs have a negative impact on health. Fuzzy Logic is a method that is able to solve existing problems where this method uses the IF – THEN function.